Corporate governance and firm performance: Evidence from Ghanaian listed companies - Kyereboah-Coleman, A.; Adjasi, C.K.D.; Abor, J. (Corporate Ownership and Control, 2006)
Well governed firms have been noted to have higher firm performance. The main characteristic of corporate governance identified include board size, board composition, and whether the CEO is also the board chairman. This study examines the role corporate governance structures play in firm performance amongst listed firms on the Ghana Stock Exchange. Results reveal a likely optimal board size range where mean ROA levels associated with board size 8 to 11 are higher than overall mean ROA for the sample. Significantly, firm performance is found to be better in firms with the twotier board structure. Results show further that having more outside board members is positively related to firm performance. It is clear that corporate governance structures influence firm performance in Ghana, indeed within the governance structures the two-tier board structure in Ghana is seen to be more effective in view of the higher firm level mean values obtained compared to the one-tier system.
Keywords: Board composition; CEO; Corporate governance; Ghana; Performance; ROA